PENGARUH PENATAAN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI DI KPP PRATAMA BALIKPAPAN BARAT - Tiko Permatasari; Abdul Hakim; Choirul Saleh (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
National development is inseparable from the State Budget as a source of state revenue, where the largest contribution to state revenue comes from tax revenues. Global and national conditions that often experience changes and are accompanied by the rapid development of the digital world have made DGT carry out tax reforms, one of which divides supervision into strategic and regional. Changes in the organization and accompanied by a strong organizational culture will encourage job satisfaction and employee performance. The sampling technique in this study used a saturated sample, with a total of 55 respondents. Data analysis using PLS-SEM (Partial Least Square). The results of research conducted in the supervision section of KPP Pratama West Balikpapan found that organizational structure has no effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, and job satisfaction has no effect on employee performance.